Health-related nudging: : A critical multimodal approach using Foucault and Habermas - Fage-Butler, Antoinette (Communication & Language at Work, 2020)
The aim of this paper is to present a methodological approach that provides analytical, critical and normative purchase on nudges’ bypassing of reflection, using a combination of multimodal analysis, Foucauldian theory, and Habermas’s (1996) concept of deliberative democracy. The approach is demonstrated using an example of a health-related nudge from the Danish context: healthy product placement in a supermaket. Multimodal analysis highlights how various modes (colour, symbol, front and back, positioning and discourse) contribute meanings to the nudge. A Foucauldian perspective provides critical perspectives on nudges as shaping practices, as short of epistemic content and thus potentially difficult to resist, and as representing a politicisation of public space. Nudges’ lack of transparency is discussed in relation to Habermas’s normative framework of deliberative democracy where recognising public perspectives and ensuring consensus are key. Limitations of the article include a smaller data set; however, the data are used to illustrate the methodological approach. On the basis of the findings, I argue for the importance of furthering critical public discourse on nudging. That way, nudgees may be better positioned to spot nudges, and the implications of policymakers using this technique of governance can be more effectively scrutinised.